Experiences of older immigrants living with dementia and their carers: a systematic review and meta-synthesis. Issue 5 (24th May 2022) - Chejor, Pelden; Laging, Bridget; Whitehead, Lisa; Porock, Davina
Abstract : Objective: To systematically review and synthesise evidence on the experiences of older immigrants living with dementia and their carers. Design: A systematic review and meta-synthesis of qualitative studies. Methods: Studies exploring the experiences of older immigrants living with dementia and their carers were eligible. Databases were searched including CINAHL, MEDLINE, PsycINFO, PubMed, Embase, Web of Science and Cochrane Library from January 2000 to April 2021. Quality assessment was undertaken using the Critical Appraisal Skills Programme checklist for qualitative studies. Data were then synthesised using the thematic synthesis approach. Results: The results of this meta-synthesis were reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement and Enhancing transparency in reporting the synthesis of qualitative research statement. A total of 3857 studies were returned from the database search. Eighteen studies were included for meta-synthesis. Five synthesised findings were identified: living with dementia and caregiving; family relationships; barriers to dementia care services; stigma and discrimination; and legal and financial issues. The experiences of living with dementia and caregiving presented multiple challenges for older immigrants living with dementia and their families. However, there seems to be very little difference between the experiences of those who have migrated to a new country and those who were born and aged in the same country, but the ability to access and use the available services is different. Conclusion: A lack of culturally appropriate dementia services, language barriers and dementia stigma can impede access to dementia care for older immigrants. Strategies to mitigate these barriers are urgently needed to ensure people from culturally and linguistically diverse backgrounds with dementia and their families have the information, education and support to access dementia services, in addition to research that explores the experiences of culturally and linguistically diverse populations. PROSPERO registration number: CRD42021277913.